2021
DOI: 10.1136/jitc-2020-002293
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric flow cytometry highlights B7-H3 as a novel diagnostic/therapeutic target in GD2neg/low neuroblastoma variants

Abstract: BackgroundHigh-risk neuroblastomas (HR-NBs) are rare, aggressive pediatric cancers characterized by resistance to therapy and relapse in more than 30% of cases, despite using an aggressive therapeutic protocol including targeting of GD2. The mechanisms responsible for therapy resistance are unclear and might include the presence of GD2neg/low NB variants and/or the expression of immune checkpoint ligands such as B7-H3.MethodHere, we describe a multiparametric flow cytometry (MFC) combining the acquisition of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…This member of the B7 family of immunomodulatory regulators is homogeneously expressed in both primary and metastatic neuroblastomas, as well as in a large variety of solid cancers, while it shows low or null protein surface expression in most normal tissues [54,55]. More specifically, a recent study found neuroblastoma patients with GD2-negative/low variants to still express B7-H3 molecule in high levels, suggesting that B7-H3 might represent an optimal alternative targetable molecule for these patients in particular [56]. At least one anti-B7-H3 monoclonal antibody has already been developed, enoblituzumab, which showed potent antitumor activity by peripheral blood mononuclear cells towards B7-H3-expressing tumors [55,57] and has been recently clinically tested in a phase I trial for solid pediatric tumors, including neuroblastoma (www.clinicaltrials.gov: NCT02982941, accessed on 21 April 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This member of the B7 family of immunomodulatory regulators is homogeneously expressed in both primary and metastatic neuroblastomas, as well as in a large variety of solid cancers, while it shows low or null protein surface expression in most normal tissues [54,55]. More specifically, a recent study found neuroblastoma patients with GD2-negative/low variants to still express B7-H3 molecule in high levels, suggesting that B7-H3 might represent an optimal alternative targetable molecule for these patients in particular [56]. At least one anti-B7-H3 monoclonal antibody has already been developed, enoblituzumab, which showed potent antitumor activity by peripheral blood mononuclear cells towards B7-H3-expressing tumors [55,57] and has been recently clinically tested in a phase I trial for solid pediatric tumors, including neuroblastoma (www.clinicaltrials.gov: NCT02982941, accessed on 21 April 2021).…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, the genetic and molecular mechanisms leading to NB development are largely unknown. In recent years, some new therapeutic approaches were developed, such as GD2 monoclonal antibodies or B7-H3 IgG antibodies, but these are not applicable in all cases [11,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GD2 monoclonal antibodies are currently used in therapy to improve standard treatments for HR-NBs, but further studies are necessary to confirm the effectiveness of this immunotherapy and to optimize it [11]. However, in 12% of patients with bone marrow relapse, NB cells lose GD2 expression, thus rendering the use of this treatment impossible [12]; for this reason, Dondero et al [13] developed a multiparametric flow cytometry to observe GD2 surface expression, suggesting B7-H3 targeting therapy for those patients in which GD2 is missed. B7-H3 is a transmembrane glycoprotein overexpressed in NB cells (particularly in bone marrow aspirates) [14], as well as in melanomas, gliomas and breast and pancreatic cancers [15].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, we observed molecular characteristics more similar to immunophenotypic variances occurring in vivo and not fully comprehended in traditional 2D culture conditions, such as the IFN-γ-induced negative regulation of PVR (CD155) expression on tumor cells after 7 days of 3D culture [ 23 ]. Moreover, it was possible to appreciate an IFN-γ-dependent upregulation of the immune checkpoint ligand B7-H3, a molecule deeply discussed above [ 179 ].…”
Section: Three-dimensional Culture Models: Moving From Spheroids To N...mentioning
confidence: 99%